The Study of Color Spectrum Curs Value Against Sunlight Color and Artificial Light for Plant Growth - Santoso , Juli; Suhardjono, Hadi; Wattimury, Agricia (Nusantara Science and Technology Proceedings)
Conventional crop cultivation systems experience several limitations, including the season, the length of day that does not match the needs of the plant, the availability of water and the narrowing of agricultural land due to population growth. Indoor farming can be a solution to overcome limitations in conventional cultivation. Indoor farming is an indoor farming system with a controllable climate, including light, temperature, evaporation and air circulation. Sunlight is the main light source in nature. Light is an electromagnetic wave that carries a form of energy. Sunlight has many functions for life on earth, one of which is as a source of energy for plants to carry out photosynthesis. Photosynthesis is a biochemical process for the formation of food substances such as carbohydrates carried out by plants. Photosynthesis takes place using chlorophyll, carbon dioxide and water and the help of sunlight energy. Sunlight consists of UV rays, visible rays and infrared rays. Visible light has a wavelength between 400 - 700 nm. Visible light is the light that plants use for photosynthesis. Chlorophyll can absorb red (600-700 nm) to blue (400-500 nm) wavelengths. The quality of sunlight is good for plant growth because it has the entire spectrum needed for photosynthesis. Artificial light from lamps that are used as a substitute for sunlight in order to support plant growth must have the quality according to plant needs. The quality of light from each source is not the same. This is the basis for conducting the study, namely comparing the quality of sunlight and artificial light sources such as lamps. Based on the studies that have been done, the color spectrum of artificial light that approaches the spectrum of sunlight is the white color spectrum. A more efficient substitute for the white color spectrum for plant photosynthesis with the pigment chlorophyll is the blue and red or growlight color combination.